ANALISIS BADAN HUKUM UNTUK KONSULTAN PAJAK SESUAI ANGGARAN DASAR IKATAN KONSULTAN PAJAK INDONESIA (IKPI) - Widya Indah Nurmalasari; Wanjuli Wanjuli (Jurnal Bisnis Terapan, 2018)
In general, the form of business activities known is Limited Company, Firma, and Persekutuan Komanditer (Commanditaire Vennotschap or commonly abbreviated as CV). Exceptions occur in the form of tax consultant business, which in accordance with Article 12 (4) of the Indonesian Tax Consultant Association (IKPI) Statute states that the business forms of the Tax Consultant of the Association Members are Individual and Civil Alliances. The reason behind the requirement of a permissible business entity is that only this civil union appears to be motivated by the nature of a private tax consultant’s permit as there is no tax consultant’s license for an agency or entity. The difference between the Civil Society and the Firm lies in Accountability that is divided into two, namely the external relations and internal relations. The Civil Society (Maatschap) is held solely for internal relationships between them without external outward influence.